PENGARUH PERSEPSI KEADILAN DALAM PEMULIHAN LAYANAN TERHADAP PERILAKU WISATAWAN PASCA PENANGANAN KELUHAN - Iswara, Agus Md Yoga; Suprapti, Ni Wayan Sri; Suasana, I G.A. Ketut Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.04.TAHUN 2016, 2016)
The purpose of this study was to explain the effect of procedural justice, distributive justice, and interactional justice on customer satisfaction of the complaint handling. In addition, this study also aimed to explain the effect of customer satisfaction of the complaint handling on consumer behaviour of trust, word of mouth, and loyalty. Subject were the customer whose stay or visiting The Ubud Village Resort & Spa, by using 150 respondents. Those sample was determining by using the purposive sampling along with analise technique data called Structural Equation Modeling with AMOS suport application tools. The result of this study found that, procedural justice, distributive justice, and interactional justice bring significant and positive impact toward customer satisfaction of the complaint handling. Meanwhile, customer satisfaction of the complaint handling brings significant and positive impacts toward customer behavioural of trust, word of mounth, and loyalty.
Keywords: Service Recovery, Perception of Justice, Consumer Behaviours